REVIEW ARTIKEL: SISTEM PENGHANTARAN OBAT SNEEDS (Self-Nanoemulsifying Drug Delivery System) DALAM FORMULASI OBAT HERBAL - Khoerunnisa, Rita; Pamudji, Jessie Sofia (Jurnal Buana Farma, 2025)
SNEDDS is a drug delivery system that aims to increase the solubility and bioavailability of drugs that are poorly soluble in water. Increased bioavailability can improve the kinetic profile of drugs in the body. This article review aims to discuss the advantages of SNEDDS formulation used to make drugs with natural ingredient extracts. The research method applied in this article is a literature review by collecting articles in the form of journals about the formulation of SNEDDS herbal medicine. SNEDDS combines various types of oils, surfactants, and cosurfactants. The selection of SNEDDS formulation composition should be done very carefully. Research and development of SNEDDS has shown the potential of SNEDDS in increasing the solubility and bioavailability of drugs that are poorly soluble in water. Although there are many challenges to be faced in SNEDDS, SNEDDS has great potential to improve the efficiency of drug therapy.